Development and Validation of the "Redi: Sang Sel Pelayar" Storybook Series for Pediatric Cancer Patients - Hanifah, Rif’at; Al atsari, Muhammad Azka; Ismail; Andira, Fiki Wahyu; Nour Hafifah, Andi Izza; Masadah, Rina; Muhiddin, Syurawasti (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study aimed to develop and validate the "Redi: Sang Sel Pelayar" storybook series as an educational tool for pediatric cancer patients, enhancing their understanding of cancer and improving treatment adherence with age-appropriate content. Using Sugiyono's R&D method, the study progressed through defining, designing, developing, and disseminating stages. Five types of childhood cancers were addressed: leukemia, retinoblastoma, osteosarcoma, neuroblastoma, and nephroblastoma. This study demonstrates that illustrated storybooks are effective in helping children understand cancer and related medical processes. The storybooks, tailored to specific cancer types and age groups with adapted characters, make it easier for children to grasp their condition. The overall average score of our readability questionnaire was 3.9, which means that our book is categorized as readable (3.4 < Mean > 4.2 = Readable). There was also a significant increase in post-test scores after the children underwent intervention by reading storybooks (P: 0.015; 95% CI 0.013–0.018). Evaluations showed significant increases in children's knowledge after reading the books, along with positive changes in their behavior and understanding of cancer. The implications for pediatric oncology care are significant, suggesting that culturally relevant educational tools can reduce anxiety and improve adherence. Despite the promising findings, the study was limited by a small sample size and a lack of long-term effect measurements. Future research should focus on larger samples and longitudinal studies to better assess the impact on adherence and well-being. Overall, the "Redi: Sang Sel Pelayar" series offers a novel approach to pediatric oncology education, with potential applications for other chronic illnesses, proposing a valuable addition to standard pediatric care practices.